Late osteosarcoma development following osteosynthesis of a diaphysial femoral fracture in a dog - SIDERI (ΑΙΚ. Ι. ΣΙΔΕΡΗ), I. K.; LOUKOPOULOS (Π. ΛΟΥΚΟΠΟΥΛΟΣ), P.; PRASSINOS (Ν. Ν. ΠΡΑΣΙΝΟΣ), N. N.; KAZAKOS (Γ. ΚΑΖΑΚΟΣ), G.; PAPADOPOULOS (Π. ΠΑΠΑΔΟΠΟΥΛΟΥ), P.; SIDIROPOULOS (Α. ΣΙΔΗΡΟΠΟΥΛΟΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Α 5.5 - year - old Great Dane was admitted for evaluation of a progressive lameness of the right hind limb of twenty days duration. The dog had sustained a mid-shaft fracture of the right femur five years ago in a traffic accident, which was initially managed unsuccessfully with the application of external stabilization, and was later successfully treated using a bone plate and screws. Radiographs revealed a fracture of the mid-shaft of the femur, under the bone plate, increased radiodensity of the surrounding soft tissues and the presence of bone spicules out of the limits of the femur. Histopathology revealed the presence of a high-grade osteoblastic productive osteosarcoma, whereas Staphylococcus spp were identified on culture. Due to the poor prognosis associated with osteosarcoma and the rapid deterioration of the dog's general condition, the owners decided to have the animal euthanized. Fractured associated sarcoma is a known, but rarely reported condition. The long-standing presence of metal implants, the tissue damage, as well as the presence of infection have been suggested as possible predisposing factors to the altered cellular activity leading to neoplasia.